2011
DOI: 10.1088/0960-1317/21/11/115026
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Si(h k l) surfaces etched in KOH solutions saturated withtertiary-butyl alcohol

Abstract: Anisotropic etching of silicon in KOH solutions saturated with tertiary-butyl alcohol (tert-butanol) was studied in this paper. The influence of KOH concentration of the solution with tert-butanol on Si(1  0  0) surface roughness and convex corners undercut were examined. It was shown that the largest reduction of convex corner undercut is achievable at low (3 M) concentration of KOH, at which, though, the (1  0  0) surface is densely covered with hillocks. The study on etch rate anisotropy and surface morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…On the other hand, with the reduction of η at 64% (C H2O2 = 0.65 M) in process, the inverted-pyramid Si textures with pronounced aspect ratio was formed owing to the existence of abundant H 2 O 2 for accelerating the cycling reaction of Cu deposition/dissolution. It should be noted that the etching rate of the Cu-induced cycling etching was more likely to be determined by breaking the surficial bonding of Si through an electroless displacement of Si with Cu 26 . Since there were no additional bias such as electric field or heat applied on this system, etching of Si was preferentially taken place at the energy-favorable sites in order to minimizing the energy barrier that was responsible for nucleation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, with the reduction of η at 64% (C H2O2 = 0.65 M) in process, the inverted-pyramid Si textures with pronounced aspect ratio was formed owing to the existence of abundant H 2 O 2 for accelerating the cycling reaction of Cu deposition/dissolution. It should be noted that the etching rate of the Cu-induced cycling etching was more likely to be determined by breaking the surficial bonding of Si through an electroless displacement of Si with Cu 26 . Since there were no additional bias such as electric field or heat applied on this system, etching of Si was preferentially taken place at the energy-favorable sites in order to minimizing the energy barrier that was responsible for nucleation.…”
Section: Resultsmentioning
confidence: 99%
“…The previous reports showed that the addition of butyl alcohols to the etching solution results in a high R(100)/R(hkl) etch rate ratio and a large reduction of convex corner undercut (Zubel and Kramkowska 2002;Rola and Zubel 2011). Therefore, in this paper, we study in detail the influence of butyl alcohols concentrations on surface morphologies and etch rates of (100) and (110) Si planes.…”
Section: Introductionmentioning
confidence: 94%
“…However, the {110} planes are patterned with stripes after etching in this solution. Saturation of the solution with butyl alcohols not only yields striped {110} planes, but also roughens the (100) surface [13]- [15]. Although the smoothness of (110) surface is improved at low alcohols concentrations (below the saturation level), the (100) surface is covered with pyramidal hillocks [16], [17].…”
mentioning
confidence: 99%